Advances towards a revision of Phalocallis: taxa of the Southeast South American Grasslands - Deble, Leonardo Paz; Keller, Hector; Moreira, Bárbara; Martin, Claudia (Balduinia, 2025)
Advances towards a revision of Phalocallis: taxa of the Southeast South American Grasslands In this first contribution towards a comprehensive revision of the genus Phalocallis (Iridaceae), deals with the species occurring in the Southeast South American Grasslands (SESA Grasslands), including those taxa that also spread beyond this region through neighboring areas. Four species are recognized: P. coelestis, P. crassispatha, P. leucopepla and P. plumbea. The first one, P. coelestis is taxonomically defined, while P. plumbea is rehabilitated from its synonym, and the main differences between both taxa are commented. Herbertia platensis is considered a new synonym of P. coelestis, while Tigridia exaltata is a new synonym of P. plumbea. Lectotypes are designated for Herbertia platensis, P. coelestis and P. plumbea. For T. exaltata, lectotype and epitype are indicated. P. crassispatha and P. leucopepla are new species proposed herein. All species are described and illustrated in detail, and information is inferred for each taxon on etymology, popular names and uses, specimens examined, phenological data, distribution and habitat, and conservation status. To enrich the information mentioned in the work, a geographic distribution map and a table with the main distinctive characteristics between the taxa are presented.